THE EFFECTS OF NICOTINE ON THE PERIODONTAL TISSUE - Herawati, Herawati; Sunariani, Jenny (Indonesian Journal of Tropical and Infectious Disease, 2010)
Tobacco contains thousands of chemical substances which known to be harmful to periodontal tissues. Nicotine was considered as the most toxic substances to periodontal tissues. The datas in this review indicate that smoking may have a significant role in the initiation and progression of periodontal destruction. The conclusion of this and the other studies indicate that smokers have a less favorable response to periodontal therapy than non smoker. Nicotine is potentially toxic substances that have a detrimental effect on periodontal tissue, by altering the host response or directly damage the cells of normal periodontium.